Auditory impairment from acoustic seal deterrents predicted for harbour porpoises in a marine protected area. Issue 8 (8th June 2021) - Findlay, Charlotte R.; Aleynik, Dmitry; Farcas, Adrian; Merchant, Nathan D.; Risch, Denise; Wilson, Ben
Abstract: Management interventions to reduce human–wildlife conflict can have unintended consequences for non‐target species. Acoustic deterrent devices (ADDs) are used globally by the aquaculture sector. However, the potential for these sound emissions to impact non‐target species, such as cetaceans, has not yet been quantified at population relevant spatial scales. To better understand the extent of potential impacts on cetaceans, such as harbour porpoises, we used acoustic modelling to investigate levels of ADD noise throughout the west coast of Scotland and across a Special Area of Conservation (SAC) for this species. Using an energy‐flux acoustic propagation model and data on aquaculture sites known to be using ADDs, we predicted the spatial extent of ADD noise on the Scottish west coast from 1 February 2017 to 31 January 2018. Noise maps were produced to determine the risk of auditory impairment for harbour porpoises under a range of scenarios which assumed single or multiple ADDs and simultaneous use across all sites. The acoustic propagation model performed well when tested against field measurements up to 5 km, with 98% of sound exposure level (SEL) predictions within ±10% of the measurements. Predictions of SELs over a 24‐hr period suggested extensive temporary hearing loss zones (median radius: ~28 km) for harbour porpoises around aquaculture sites. Assuming a single device at each site, 23% of the harbour porpoise SAC was predicted to be exposed to ADD noise sufficient to induce a temporary threshold shift, and under the worst‐case scenario (multiple, continuously running devices per site with an aggregate duty cycle of 100%), levels exceeding permanent threshold shift could reach 0.9% of the SAC. Policy implications . This study highlights the potential for 'collateral damage' from interventions such as acoustic deterrent devices (ADDs) which are intended to reduce human–wildlife conflicts with pinnipeds but may affect the long‐term health and habitat use of non‐target species. This is especially true for harbour porpoises which are protected under the EU and UK Habitats Regulations. The aquaculture industry, policymakers and regulators in countries where ADDs are used should consider these findings when attempting to mitigate pinniped depredation. Abstract : This study highlights the potential for 'collateral damage' from interventions such as acoustic deterrent devices (ADDs) which are intended to reduce human–wildlife conflicts with pinnipeds but may affect the long‐term health and habitat use of non‐target species. This is especially true for harbour porpoises which are protected under the EU and UK Habitats Regulations. The aquaculture industry, policymakers and regulators in countries where ADDs are used should consider these findings when attempting to mitigate pinniped depredation.